Pengaruh Beban Kerja Terhadap Kinerja Karyawan Di Hotel Plataran Bromo - Rara Ayu Khotimah; Yuliana Yuliana (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
The inspiration for this study arises from various challenges, including a workload that sometimes feels overwhelming, frequent breakdowns in communication during task handling, and employees having to adapt to consecutive shifts. The primary aim of this research is to assess the impact of workload on the performance of Plataran Bromo Hotel employees. Employing a quantitative approach with a causal associative method, the study utilizes both primary and secondary data. The participants consist of the workforce at Plataran Bromo Hotel, and data collection involves a validated survey with a Likert scale. The gathered information undergoes analysis using SPSS 27.00. The findings reveal that the workload is categorized as